2008
DOI: 10.1111/j.1572-0241.2007.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Autoimmune Pancreatitis With Cytotoxic T-lymphocyte Antigen 4 Gene Polymorphisms in Japanese Patients

Abstract: Objectives: Autoimmune pancreatitis (AIP) is characterized by high serum IgG4 concentrations, lymphoplasmacytic inflammation, and a favorable response to corticosteroid treatment. Although the HLA DRB1*0405-DQB1*0401 haplotype and Fc receptor-like 3 polymorphisms have been associated with AIP, the role of other genetic factors is largely unknown. As cytotoxic T lymphocyte antigen 4 (CTLA4) polymorphisms have recently been linked with several autoimmune diseases, we sought to determine if CTLA4 polymorphisms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 35 publications
5
90
0
2
Order By: Relevance
“…A possible genetic association between CTLA-4 polymorphism and AIP has been shown [62,64]. In addition, a recent study has shown that serum sCTLA-4 levels are increased in AIP [62].…”
Section: Sctla-4 and Autoimmune Diseasesmentioning
confidence: 98%
See 3 more Smart Citations
“…A possible genetic association between CTLA-4 polymorphism and AIP has been shown [62,64]. In addition, a recent study has shown that serum sCTLA-4 levels are increased in AIP [62].…”
Section: Sctla-4 and Autoimmune Diseasesmentioning
confidence: 98%
“…Increased serum levels of sCTLA-4 have been reported in patients with several autoimmune diseases significantly more often than in healthy individuals [20, 33, 49-51, 60, 62]. Patients with GD [20,33,49], HT [20,49], MG [50], systemic lupus erythematosus [55], systemic sclerosis (SSc) [54], CD [51], autoimmune pancreatitis (AIP) [62] and spondyloarthropathies and RA [60] have been investigated. The first studies on sCTLA-4 serum levels in autoimmune disease were performed 10 years ago [20] in 17 patients with GD and 3 patients with HT.…”
Section: Sctla-4 and Autoimmune Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The cytotoxic T-lymphocyte antigen 4 (CTLA4) polymorphism has been reported to be another predictor of AIP recurrence. 13 CTLA4 is an inhibitory receptor expressed on the cell surface of activated-memory T cells and on regulatory T cells; it acts largely as a negative regulator of T-cell responses by modulating positive T-cell costimulatory signals on antigen-presenting cells. Single nucleotide polymorphisms (SNPs) in CTLA4, termed +49A/G, have been specifically associated with susceptibility to autoimmune diseases, including type 1 diabetes, autoimmune thyroid disease, autoimmune hepatitis, and primary biliary cirrhosis.…”
Section: Prediction Of Recurrence By Serum Markersmentioning
confidence: 99%